2023
DOI: 10.2176/jns-nmc.2022-0229
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Treatment of Chronic Subdural Hematoma with Gorei-san

Abstract: Most asymptomatic patients with chronic subdural hematoma (CSDH) are followed conservatively but can require surgical treatment if the hematoma expands. We conducted a retrospective evaluation of the effect of Gorei-san on CSDH. This study included patients treated between April 2013 and March 2015. In total, 289 patients were diagnosed with CSDH and 110 patients received conservative management. Finally, 39 patients who met the requirements were registered. We retrospectively examined the age, gender, medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, it is possible that regulating aquaporins could lead to improvements in peritumoral edema. Goreisan, a herbal medicine used in Japan and other Asian countries (known as Wu Ling San in China and Oreongsan in Korea), is considered to inhibit edema through downregulating aquaporin 4 expression [96][97][98][99]. Studies have demonstrated its efficacy in reducing cerebral edema following stroke [100].…”
Section: Aquaporin Inhibitorsmentioning
confidence: 99%
“…Nevertheless, it is possible that regulating aquaporins could lead to improvements in peritumoral edema. Goreisan, a herbal medicine used in Japan and other Asian countries (known as Wu Ling San in China and Oreongsan in Korea), is considered to inhibit edema through downregulating aquaporin 4 expression [96][97][98][99]. Studies have demonstrated its efficacy in reducing cerebral edema following stroke [100].…”
Section: Aquaporin Inhibitorsmentioning
confidence: 99%
“…Clinical studies have also reported that ORS is effective in preventing calcium oxalate nephrolithiasis [8]. In addition, ORS was found to reduce gastrointestinal adverse reactions in patients taking selective serotonin reuptake inhibitors (SSRIs), and it was proven to reduce hematoma in patients with chronic subdural hematoma (CSDH) [9,10]. Traditional Oriental medicines (TOMs), which include prescriptions such as ORS, are widely used to prevent diseases, owing to their efficacy and low toxicity [11].…”
Section: Introductionmentioning
confidence: 99%